DESIGN OF LOCAL TUBER PROCESSING PLANTS BASED ON GREEN TECHNOLOGY: ENERGY EFFICIENCY AND WORK SAFETY STUDY - Yoedi Wicaksono (RADJA PUBLIKA, 2025)
This research aims to design a local tuber processing plant, especially cassava, into a value-added processed product with a green technology approach. The main focus of this research is on energy efficiency and the application of occupational safety (K3) in the production process. The methods used include literature studies, field surveys, production process design, energy consumption analysis, and work risk identification using the Hazard Identification and Risk Assessment (HIRA) approach. The design results show that the plant's energy consumption can be reduced by up to 26.4% through the application of solar ovens and biomass-fueled heaters. In addition, the plant layout system is designed to support process flow efficiency and energy savings through natural lighting. From the aspect of occupational safety, seven risk points were successfully identified and mitigated through technical engineering, safe work procedures, and the use of personal protective equipment. Design validation by experts shows that this design is feasible to be implemented in local tuber center areas and can be a model for a small-medium-scale eco-friendly food industry. This research proves that local food processing can be developed efficiently, safely, and sustainably with an appropriate and contextual technological approach.